Factors influencing managers’ CSR decisions: a research framework - Darwin, Eka Noorul Baitie; Alias, Siti Noormi; Omar, Zoharah; Mohd Anuar, Mohd Ashraff (Human Resource Management Academic Research Society, 2021)
Although numerous studies have investigated the role of managers in making CSR decisions, not many offer findings on factors affecting managers’ decisions in engaging with CSR activities. Some studies discuss CSR practices by highlighting factors that directly influence CSR implementation in the organization but do not focus on managers as individuals playing a vital role in deciding CSR. Other than that, no study was found using Upper Echelons Theory and Model of Strategic Decision-Making Effectiveness to examine such factors. Thus, this study aims to fill the gap in the literature by identifying factors affecting managers’ CSR decisions based on respected theory and model. The findings should help future researchers to study in greater depth on influence of managers’ characteristics and their psychological makeup, organizational characteristics and also external characteristics on managers’ CSR decisions. HRD practitioners also can consider the contributing variables when plan strategies for CSR implementation for the organization.